Cosmic Humanity: Utopia, Realities, Prospects - Sergey Krichevsky (International Society of Philosophy and Cosmology, 2017)
The philosophical foundations of the theory and practice of the creation of cosmic humanity as a process of the evolution of human civilization, the emergence into space, with the prospect of resettlement outside the Earth are considered. There is a connection between myths, fantasies, ideas, concepts and projects aimed at the exploration of outer space, the creation of cosmic humanity. A new and voluminous definition of cosmic humanity in the evolutionary paradigm is given. Cosmic humanity is (essence and 4 stages of evolution): 1. Humanity living on Earth, sensing, knowing, understanding its cosmic origin, relationship with the cosmos and cosmic destiny. 2. Humanity living on Earth, leading aerospace activity for the purposes of exploration and use of aerospace space (Heaven, Space) for survival and development. 3. Humanity living on Earth and outside the Earth - in the solar system, preserving the Earth and mastering the Cosmos for survival and development. 4. Humanity, settled and living in the Cosmos. Now humanity is in the process of transition from the second to the third stage. In the process of this evolution, a complex transformation of man and society takes place. The problem-semantic field of cosmic humanity is described and its general model is presented. The meta-goal-setting is the justification of cosmic humanity with the application of the anthropic principle and its "active" super (post) anthropic supplement: "Cosmic humanity has an evolutionary purpose to actively manage evolution: change man, humanity and the universe." The evolution of the "cosmic dream", goals and technologies of space activities is formalized in the form of a conceptual model. Challenges and negative trends are considered in connection with the crisis of space activity, criticism and attempts to limit the flights of people into space. The prototype of cosmic humanity, its basis and acting model is the cosmonauts' community. The main characteristics and tendencies of the development of the world cosmonaut community for 55 years of spaceflight, indicators of national competitions in selecting cosmonauts as indicators of the society's attitude to cosmonautics and the cosmic future of humanity are given. The main results, consequences and prospects of spacewalk in the context of the evolution of technology, human and humanity, including the main potentialities, challenges and threats caused by technical development, the creation of a posthuman, etc., are considered. The description and analysis of the social mega-project of the new space state ASGARDIA, which is created since October 2016 and is the institutional basis of cosmic humanity, is given. In fact, it is a state for the future of cosmic humanity, which has already begun (itself) to be organized on Earth. There is a process of transformation of the almost fantastic and superglobal utopia of the first in the history of the earthly civilization of the cosmic state of people - the "cosmic international" - into the reality of a fundamentally new social contract. The idea and the project of the space state is exactly what was lacking for the process of space expansion to go seriously: a new geocosmopolitan subject and an actor who is interested in space exploration (including resettlement in it in the long run) as in its main goal and overarching goal, and Focused on this process. The first results of the project are encouraging. An interesting sociological model is being created, based on an analysis of the statistical relationships of the present earthly and promising cosmic humanity. The first, unique, but important and unique "cosmic referendum" on the Earth is being held. The characteristics of the state being created are shown, citizens of which expressed a desire to become about 600 thousand people from more than 200 states, of which over 170 thousand people are certified as citizens and the process continues. A "cosmic" coefficient was proposed to assess the activity of citizens of the countries of the Earth in the ASGARDIA project and its values were obtained for the leading group of countries. The main problems, scenarios and prospects of the project implementation are considered. The main conclusions and recommendations are given.